Al-Hafiz Al-Dhahabi’s corrections of the hadith scholars in their judgment on the hadith in his book “Al-Seer”, a collection and study - Ahmed , Hamad (Islamic Sciences Journal, 2023)
Imam al-Dhahabi is one of the imams of hadith, and one of the most prominent imams of jarh and ta’deel, and his book “Siyar A’lam al-Nubala’” is one of the most important books of biographies that have been translated for hadith scholars and others. This book contains many benefits in the sciences of the noble hadith and other sciences. Scholars called it the hadith of the Prophet, and al-Hafiz al-Dhahabi reconciled some imams in their ruling on the hadith. Because of the importance of these corrections in highlighting an important aspect of the personality of Imam Al-Dhahabi, which is the distinct and balanced critical mentality, and for its scientific importance, I tracked it, then collected it, and then studied it by following the analytical inductive scientific method, and named the research: “The Remedies of Al-Hafiz Al-Dhahabi on the hadith scholars in their judgment on the hadith in his book Al-Sir His plan came in an introduction, two chapters, and a conclusion: The first topic: introducing Al-Hafiz Al-Dhahabi, his biographies, and the meaning of rectification in language and terminology. The second topic: Al-Hafiz Al-Dhahabi's corrections of the hadith scholars in their judgment on the hadith. As for the conclusion, I mentioned the most important findings and recommendations.